Where can the elderly walk? A spatial multi-criteria method to increase urban pedestrian accessibility. (August 2022) - Gaglione, Federica; Gargiulo, Carmela; Zucaro, Floriana
Abstract: In terms of residual physical activities suitable for most elderly individuals, walking is also the favoured form of mobility in this group, in particular for those aged 75 and over. For this segment of the population, walking represents the main means of accessing urban services and actively participating in community life. It is thus essential to improve both the physical and functional organization of urban areas to develop comfortable and safe walking paths for the elderly and the other weak segments of population. Therefore, this study provides a methodology for classifying a neighbourhood as more or less accessible for the elderly to reach urban services on the basis of its favourable characteristics. Based on the results of a literature review and Delphi analysis, the fuzzy technique was applied to evaluate the security and urban context characteristics, both in terms of the pedestrian network and built environment. The obtained weights, validated by a sensitivity analysis, were then used to calculate a walking attractiveness index for the elderly using a GIS tool. The methodology was then tested in two neighbourhoods of Naples; the outputs show the areas that local decision-makers should prioritise to improve the safety and attractiveness of routes to access urban services. Highlights: The paper explores urban pedestrian accessibility for elderly. The method measures urban pedestrian friendliness by integrating FAHP, sensitivity analysis and GIS. The method is tested in Naples, Italy. Results indicate the usefulness of the approach to policymakers.